2019
DOI: 10.3390/cells8060524
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Gene Polymorphism and Urinary OPN Excretion in Patients with Immunoglobulin A Nephropathy

Abstract: Osteopontin (OPN) is a glycoprotein involved in the pathogenesis of multiple autoimmune and inflammatory conditions. However, the association of variants of secreted phosphoprotein 1 gene (SPP1), which encodes OPN, with immunoglobulin A nephropathy (IgAN) has not been examined up to date. Moreover, the role of OPN in disease pathogenesis and clinical manifestations is not fully known. Therefore, the aim of the study was to determine the frequency of four single nucleotide polymorphisms (SNiPs) of SPP1 gene, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…However, OPN as a factor for discriminating between various kidney diseases has not yet been fully explored. In previous research, our team focused on the link between OPN gene polymorphisms and excretion of uOPN in patients with IgAN [9]. In the present study, we compared uOPN in various immune-related glomerulopathies.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, OPN as a factor for discriminating between various kidney diseases has not yet been fully explored. In previous research, our team focused on the link between OPN gene polymorphisms and excretion of uOPN in patients with IgAN [9]. In the present study, we compared uOPN in various immune-related glomerulopathies.…”
Section: Introductionmentioning
confidence: 94%
“…The role of OPN in glomerular diseases is not clearly defined. OPN gene polymorphisms are associated with the development of diabetic nephropathy in type 2 diabetes [8], urinary OPN (uOPN) excretion in patients with IgA nephropathy (IgAN) [9], and acute renal allograft rejection [10]. OPN mRNA expression in tissue is increased in areas of tubular damage [11] and in patients with renal calculi [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the past several specific SPP1 gene variants have been associated with the pathogenesis and progression of different kidney diseases. Other case-control studies reported on specific variants in the SPP1 gene being associated with different kidney disease patients in comparison to a (healthy) control group: For example, rs1126616 was repeatedly reported as a marker for lupus nephritis and immunoglobulin A nephropathy [ 10 14 ]. In connection with diabetic nephropathy, the two SNPs in SPP1 , rs11730582 and rs17524488, have been reported [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both GNs are classified as rare diseases with ORPHA numbers 761 and 97560, respectively, without targeted treatment or prognostic markers, yet. Recent years have brought new insights into a molecular background of GNs, especially in the field of -omics (genomics, transcriptomics, and proteomics) [2][3][4][5][6][7]. These discoveries revealed pathophysiologic mechanisms, which could be helpful in the development of biomarkers and targeted therapy in the future.…”
Section: Introductionmentioning
confidence: 99%